Influence of Wilson’s understanding of dichotomy on the development of modern public administration - Milenković, Dejan (Sociološki pregled, 2024)
Public administration is a complex social phenomenon which has its own sociological, political, legal, organizational and other features. Accordingly, the “angle” of its observation can be quite different. Public administration is therefore studied in numerous higher education institutions, both in the field of political science, sociology, law and others. Woodrow Wilson, former US president and the Nobel Prize winner, is considered the founder of the scientific approach to administration. In his scientific work from 1887, entitled “The Study of Administration”, Wilson pointed out three “dichotomies” related to public administration: (1) between politics and administration; (2) between political and administrative sciences, and (3) between politicians and civil servants. Wilson thus raised a whole series of issues that are still the subject of polemics and discussions, and his scientific thought has become a permanent legacy and the subject of study by numerous authors in both theoretical and practical analysis of public administration, which still has an impact on its changes and development.